Curcumin's Potential as a Therapeutic Agent for Hpv-Induced Cancer - Triani Nur Fitri; Adilla Syahsiyatun Najah; Syifa Salsabila Mulyani; Wulan Pertiwi (Indonesian Journal of Engineering and Technological Innovation, 2025)
Curcumin, the main active compound of turmeric (Curcuma longa), shows potential as a therapeutic agent for Human Papillomavirus (HPV)-induced cancer. This study examines the mechanism of action of curcumin in inhibiting the proliferation of HPV-infected cervical cancer cells, including its anti-inflammatory, anti-cancer, and anti-viral properties reviewed from several references. Curcumin works by suppressing the expression of E6 and E7 oncoproteins, induction of apoptosis, and modulation of signaling pathways that support tumor growth, such as NF-κB. Although curcumin has great potential, the challenges of low bioavailability and rapid metabolism in the body still need to be overcome. Further research is needed to optimize the formulation and delivery method of curcumin as a cancer therapy.